Measuring thyroglobulin autoantibodies by sensitive assay is important for assessing the presence of thyroid autoimmunity in areas with high iodine intake - Ito, Kunihiko; Noh, Jaeduk Yoshimura; Ueda, Miki; Okamoto, Yasuyuki; Konishi, Toshiaki; Fujisawa, Toshimichi; Ito, Koichi; Hamada, Noboru (Endocrine Journal, 2010)
There is some debate over the clinical utility of measuring serum TgAb to assess the presence of thyroid autoimmunity. To clarify the relationship between TgAb levels and thyroid autoimmunity, a histological examination of thyroid tissue was carried out on unselected living individuals with detectable serum TgAb. 146 patients with a pathological diagnosis of follicular adenoma were selected as subjects. Focal lymphocytic infiltration (FLI) was defined as lymphocytic aggregates of more than 200 in number. A thyroid gland in which 0-1 FLI was observed in a few visual fields of low magnification (20 × 4) in thyroid tissue adjacent to a tumor was judged to be normal and a thyroid gland in which 2 or more FLI were observed was diagnosed as focal lymphocytic thyroiditis (FLT). Serum levels of TgAb and TPOAb were measured by radioimmunoassay. Out of the 146 patients, 18 had detectable serum TgAb and 16 had detectable serum TPOAb. All but one (i.e. 94%) of the 18 TgAb positive patients had FLT and 14 out of the 16 TPOAb positive patients had FLT. The sensitivity (17/32; 53.1%) and specificity (113/114; 99.1%) of TgAb for detecting FLT were higher than those (14/32; 43.7% and 112/114; 98.2%) of TPOAb, but the differences were not significant. In 9 patients who were TgAb positive (but TPOAb negative), 8 (88.9%) had FLT. These results throw doubt on the Laboratory medicine practice guidelines published in Thyroid 2003, in which measuring TgAb is not usually necessary for detecting autoimmune thyroid disease. At least measuring TgAb by sensitive assay is useful for assessing the presence of thyroid autoimmunity in Japan, an area with high iodine intakes.